Magnetic solid-phase extraction of bisphenol A from water samples using nanostructured material based on graphene with few layers and cobalt ferrite - Oliveira, Rhayza Victoria Matos; Santos, Alessandra Ferreira; Santos, Maria Danielly Lima; Cunha, Graziele da Costa; Romão, Luciane Pimenta Cruz [UNESP] (My University, 2022)
In this study, magnetic hybrid materials composed of cobalt ferrite, natural organic matter, and graphene (CoFe2O4/NOM/graphene) were synthesized and applied as adsorbents in the magnetic solid-phase extraction (MSPE) of bisphenol A (BPA) from aqueous matrices. To our knowledge, no studies have been previously conducted using this material for MSPE. Techniques including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy and transmission electron microscopy (TEM) were used to investigate the composition and morphology of the adsorbent. The MSPE method was optimized considering the main parameters influencing the process, with the best results obtained using 50.0 mg of adsorbent, agitation at 150 rpm, total extraction time of 7.5 min, 10 mL of methanol as extractant, and pH between 4 and 10. BPA analysis was performed using HPLC-DAD and HPLC-FL, with the latter showing better sensitivity. The developed method provided a wide linear range from 0.1 to 5000 μg L−1, with limits of detection (LOD) and quantification (LOQ) of 0.022 and 0.072 μg L−1, respectively. The extraction procedure presented reproducibility (RSD) of 2.13–2.21% and excellent recoveries in the range 99.3–104%. The developed MSPE method using CoFe2O4/NOM/graphene proved to be simple, fast, and efficient for the analysis of BPA in a variety of aqueous matrices.
Keywords: Endocrine disruptor; Liquid phase exfoliation; Magnetic hybrid; Nanoparticles; Natural organic matter; Solid phase extraction